Adopsi Cashless Payment System pada Industri Kuliner di Kota Makassar: Pendekatan UTAUT Model - Astuty Hasti; Asriah Syam (AkMen JURNAL ILMIAH, 2023)
This research uses the Unified Theory of Acceptance and Use of Technology (UTAUT) model to measure the readiness of culinary industry players in Makassar City to adopt a non-cash payment system in the businesses they run. This research is a quantitative research using a purposive sampling technique, with a total sample of 183 culinary industry entrepreneurs. Data analysis in this research uses AMOS in testing structural equation models. Performance expectations, social influence, facilitation conditions directly have a significant positive effect on behavioral intentions and perceived risk. Meanwhile, effort expectations directly have an insignificant effect on behavioral intentions and perceived risk. The results of statistical tests show that perceived risk is able to mediate the influence of performance expectations, social influence, and facilitating conditions on behavioral intentions. However, perceived risk was unable to mediate the effect of effort expectations on behavioral intentions. The results of this research show that high-level UTAUT dimensions are able to reduce the risks felt by culinary industry entrepreneurs and increase the use of cashless payment systems in transactions.